Alcohol Interventions on Online Grocery Shopping Platforms - Vigh, Eszter; Attwood, Angela; Roudaut, Anne (International Journal of Population Data Science, 2024)
Introduction & Background There is opportunity to engage light to moderate drinkers in alcohol reduction interventions as a preventative measure. In the space of online grocery shopping there is an added challenge in intervention development in the form of deceptive patterns, which influence consumer behaviour in unhealthy ways including automating behaviour and encouraging overconsumption. Objectives & Approach The objectives of this study are to: 1) identify deceptive patterns in the online grocery shopping context, 2) develop interventions which support healthier decision making in this context, 3) apply those interventions to appropriate product categories. The method utilised in the first objective is heuristic analysis which was conducted across eleven major online grocery shopping platforms. The interventions were then developed using the Rapid Iterative Testing and Evaluation (RITE) method, which involved interviewing participants and iterating upon the inventions after every interview. Each interview was analysed using content analysis. When incorporating the interventions into the online grocery shopping environment, interviews were conducted to gain insight into drinking and purchasing habits of consumers. These final interviews were then analysed with inductive thematic analysis. Relevance to Digital Footprints Digital Footprints underpin the entire intervention development space. The background of the project is built upon human shopping and interaction behaviour online when encountering deceptive patterns. These deceptive patterns have been established using mobile gaming micro-transaction data, online grocery shopping log-in and rewards data, among other data sources. Digital Footprints data can further support the findings from the thematic analysis by further showing cultural and social trends around drinking (e.g., increased purchasing of seasonal beers and ciders in the summer and during sporting tournaments). The purpose of the drinking identified through those social and cultural trends gauge the appropriateness of proposed alcohol interventions. Beyond this, digital footprints data around engagement with health and wellness promoting applications (e.g., active users and app downloads) provides greater insight into the types of health messaging that garner attention and can be used to further inform how to approach those currently outside the health-engaged group. Digital footprints serve to attach larger societal trends to the smaller-scaled interviews and thematic analysis conducted as part of the study. Results Initial findings have shown opportunities for nudging light to moderate drinkers who primarily consume beer, wine, or cider. Spirits have been identified as difficult to substitute due to a lack of substitution options in the low alcohol spirit category that are widely available on the consumer market via online grocery retailers. Conclusions & Implications Without significant change, costs to the National Health Service (NHS) in alcohol related harm are set to rise by over 1 billion GBP. Alcohol consumption is a public health risk and there are opportunities to utilise digital footprint informed interventions to engage the public in preventative interventions.